Task‐free functional networks related to emotion processing in frontotemporal lobar degeneration. (31st December 2021) - Canu, Elisa; Calderaro, Davide; Castelnovo, Veronica; Leocadi, Michela; Basaia, Silvia; Filippi, Massimo; Agosta, Federica
Abstract: Background: Nonverbal communication is a crucial aspect of interpersonal relationships, and defective emotion recognition can lead to altered social interactions. The aim of our study was to investigate the relationship between emotion processing and resting‐state functional connectivity (RS‐FC) in frontotemporal lobar degeneration (FTLD). Method: 80 FTLD patients and 65 age‐matched healthy controls underwent brain 3.0 Tesla MRI [3DT1‐weighted and RS‐functional MRI (RS‐fMRI)] and neuropsychological assessment, including the Comprehensive Affect Testing System (CATS). FLAME models in FSL were performed between each emotion construct and RS‐FC changes within crucial networks. Result: FTLD patients performed worse than controls in all CATS‐subtests. In controls, a high performance at the emotion naming and emotion matching constructs was related with increased RS‐FC within the cerebellar network, and a high performance at the emotion discrimination construct was related with increased RS‐FC of the right occipital face area (OFA) within the visuo‐associative network. In FTLD patients, high performances at the emotion naming construct were related with increased RS‐FC of the bilateral OFA within the visuo‐associative network and the bilateral frontal pole within the default‐mode‐network, whereas high performances at the emotion matching construct were related with increased RS‐FC of the left OFA within the visuo‐associative network. Finally, in FTLD patients, high performances at each emotional construct were related with decreased RS‐FC within the basal ganglia network. Conclusion: In healthy controls and FTLD patients, the RS‐FC within crucial networks is related to different constructs of emotion processing. In FTLD, the RS‐FC associated with emotional performances involved a large number of brain regions, likely due to brain functional specificity loss and compensatory attempts. These findings offer potential markers for detecting functional vulnerability linked to social interactions. Disclosures . Supported by the Italian Ministry of Health (GR‐2013‐02357415); European Research Council (StG‐2016_714388_NeuroTRACK).